Instructional Decision-Making as a Framework to Connect Theory and Practice in Language Teaching : The Case of Focus on Form (2007)
ABSTRACT: This paper explores the framework of Instructional Decision-Making (IDM) as a means to connect theories in Second Language Acquisition (SLA) with practice in language teaching and learning. For this purpose, the author examines the pre-active, interactive, and post-active stages of IDM and how Focus on Form (FonF) can be applied within the classroom. This review reinforces the necessity of making theories in SLA more applicable for language teachers, highlights the potential of IDM to attain this connection, and shows the benefits and limitations of FonF as a pedagogical proposal for language teachers. The paper concludes by presenting implications for research and practice.